История & этика: формирование новой историографической культуры - Маловичко, С. (Інститут історії України НАН України, 2008)
This article investigates a problem “history and ethics”. Recently some historians even more often speak about “implicit ethics” in the historical writing, on ethical responsibility of a historiography before dead “Others” or before the proceeding present. The author considers, that in spite of the fact that the historiogr aphy persistently rejects ethics, last is already entered into the theory sociohumanitarian knowledge. Ethics become one of tools of new historiographic culture.